Simulation OSEs (Observed Structured Educational Stations) to Develop Inter-Professional Education (IPE) and Collaborative Working (CW) in Healthcare at Cygnet Churchill Hospital London, UK - Angela Misra; Omer Malik; Yugisha Gurung (BJPsych Open, 2025)
Aims: Calhoun et al. assessed the effectiveness of in-situ simulation education and showed that adding in-situ simulation to current educational practices may improve patient mortality and morbidity.